“Escola segura terra”: educação escolar Guarani e Kaiowá como ferramenta de luta pelo tekoha - Cruz, Hildyanne Teixeira Costa (2022)
This research aims to raise new data that give continuity to ongoing research on the Guarani and Kaiowá in struggle for the recognition of their rights in order to understand the relationship between the struggle for territory and school education projects within the communities. In Dourados, Mato Grosso do Sul, the most populous indigenous reserve in Brazil is located. With about 17 thousand people, families of the Kaiowá, Guarani and Terena ethnic groups live in the village. This territory is known, nationally and internationally, for the precariousness in which the peoples who reside there live and for the situations of violence to which they were subjected after being expelled from their traditional territories and collected in small areas demarcated by the Indian Protection Service ( SPI). But the Guarani and Kaiowá are also known for the responses they have been giving to the attacks on their rights through the retaking of traditional territories, identified by them as tekoha. The struggle for land appears as the main means of solving the problems currently faced by the Guarani and Kaiowá. During my experience with the Guarani and Kaiowá I was able to observe that the fight for education is linked to the fight for land. Thus, the communities involved in processes of recovery of traditional territories have given special attention to education projects, becoming of great importance to help in the struggle for tekoha and teko porã. This project seeks to recognize the impasses faced by the Guarani and Kaiowá in the struggle for indigenous school education. Although the guidelines for indigenous education are set by the State itself, recognizing the limitations given by it, the indigenous people seek to change its character, so that the school can be an instrument in the struggle for land. Based on a research with an ethnographic bias carried out in the resumption of Nhu Porã, i bring up the dilemmas that communities in non-demarcated areas face for the realization of an indigenous education aimed at autonomy.